Design of environmental monitoring and control system in climatic chamber for True Shallot Seed (TSS) seedlings based on the internet of things - Solahudin Mohamad; Sucahyo Lilis; Kumala Ayu; Widodo Slamet (BIO Web of Conferences)
The microclimate and environmental conditions during the shallot seedling stage significantly influence growth quality. Therefore, a robust monitoring and control system within the climatic chamber is essential to ensure optimal conditions and adjust parameters throughout the cultivation process. This study aims to develop a system for monitoring and controlling the climatic chamber environment and to evaluate the performance of the implemented system. The research involved several stages: system analysis, design, testing, and performance evaluation. The electronic components and sensors include DHT21, DS18B20, BH1750, ESP8266 microcontroller, and 4-channel relays. The monitoring results show that the climatic chamber's temperature ranged from 20.25–22.79 °C ± 0.64, the humidity level was 77.66‒89.31% ± 2.11, and LED light intensity was 2800–2900 lux ± 10.55. The monitoring system was successfully designed using the Blynk Internet of Things (IoT) application to track environmental parameters in the automated climatic chamber. The control system was also developed using the millis syntax and the net time protocol (NTP) module in the Arduino IDE, enabling parameter control based on scheduled on/off durations.